(3eONd Edi HMhK GdYedjGJ (B/s - (3GdTeQJj, MGeO SYO fhQs; (3GdRHjOj, Ydj Ndjds ((3YeGf(B: s (3OGQ GdeLOdGhj(B, s, 2007)
(3GdaUd GdGhd (B: (3GdHQeLI GdNWjI (B: (3GdeONd (B: (3fTCI HMhK GdYedjGJ (B: (3eSGFd JhVjMjI (B: (3WQGFb Md GdHQeLI GdNWjI (B: (3WQjb GdSeHdcS (B: (3WQjbI GdSeHdcS PGJ GdeQMdJjf (B: (3fXQjI GdebGHd (B: (3GdTQhW GdhgejI GdJcejdjI (B: (3WQjbI GdeSHdcS GdeYOdI (B: (3WQjbI GdeSHdcS HhGSWI GdJLRFI (B: (3WQjbI GdeSHdcS h GdeJZjQGJ GdeMOOI(B-(3GdaUd GdKGfi (B: (3GdeHQeLI GdNWjI GdUMjMI (B: (3GdeONd (B: (3eSGFd JhVjMjI (B: (3WQGFb Md eSGdI GdHQeL GdNWjI GdUMjMI (B: (3GdHQeLI GdKfGFjI(B-(3GdaUd GdKGdK (B: (3GdHQeLI GdNWjI GdeYedjI (B: (3GdeONd (B: (3GdJZjjQ ai (BC : (3GdJZjjQ ai (Bb : (3GdJZjjQ ai (BPj : (3GdJZjjQ ai (Bb (3h (Bc-(3GdaUd GdQGHY (B: (3eSGdI Gdfbd (B: (3GdeONd (B: (3Jchjf GdfehPL Gdfbd (B: (3UjGZI GdfehPL HQeLI NWjI (B: (3eSGFd JWHjbjI (B: (3GjLGO GdMd GdGhdi Md eSCdI GdJbd ZjQ GdeJhGRfI (B: (3eSCdI GdJYXje(B-(3GdaUd GdNGeS (B: (3JMdjd GdeNWWGJ GdTHcjI(B-(3GdaUd GdSGOS (B: (3fXQjI GdeHGQGI (B: (3GdeONd (B: (3eHGQGI GdTNUjf PGJ GdeLehY GdUaQi (B- (3GdaUd GdSGHY (B: (3fXQjI Uaha GdGfJXGQ (B: (3JWHjbGJ Uaha GdGfJXGQs
(3HjHdjhZQGajG U(B.519s
Keywords: (3GOGQI GYeGds; (3GOGQI JfajPjIs; (3HMhK GdYedjGJs